Relações "in-group-out-group" e o processo de desenvolvimento - Nogueira da Gama, Célio (Revista Ceres, 2025)
The author, using a critical analysis of several approaches to economic development which are oriented by an ideology of modernization, suggests a model of analysis at the level of cultural relations between rural and urban systems in any specific society. This model of analysis is based on the "in-group-out-group" relations that are in correlation with the situation or field variable of Lewin's theory. The author pretends, with this model of analysis, to obatin the totality of development process, in order to get the cultural elements that interfer in the phenomenon of the obstacles to change.